Kepemimpinan Kepala Desa Dalam Meningkatkan Kinerja Perangkat Desa Nusa Agung Kecamatan Belitang III Kabupaten Ogan Komering Ulu Timur - Rindy Putri Hapsari; I Gusti Made Darma; Ariyanto Ariyanto (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
The importance of the leadership role for a leader lies in his ability to set an example through attitudes and actions, which in turn creates a positive work environment. This study aims to analyze the role of the Village Head's Leadership in Improving the Performance of Nusa Agung Village Apparatus in Belitang III District, East Ogan Komering Ulu Regency. The research method used is qualitative descriptive analysis. The results showed that the leadership of the Village Head was not optimal, with the lack of discipline of the Village Apparatus due to less strict supervision and the lack of regulations applied to encourage work discipline.